Senior High School Students' Numeracy in Solving Number Content AKM Problems in View of Adversity Quotient - Toni Phibeta; Rooselyna Ekawati; Atik Wintarti (Universitas Negeri Surabaya, 2025)
Numeracy is the ability of students to identify information, use mathematical facts and procedures, and evaluate results or mathematical ideas represented in various forms to solve problems in everyday life. Meanwhile, the Adversity Quotient (AQ) refers to a person's ability to endure and persevere through various events that cause difficulties or challenges. The aim of this study is to describe the numeracy skills of senior high school students in solving AKM (Minimum Competency Assessment) questions on number content, viewed from the perspective of Adversity Quotient (AQ). The type of research used is descriptive research with a qualitative approach. The research subjects consisted of one representative student for each AQ category, selected purposively to allow an in-depth exploration of numeracy processes. The research instruments included the ARP (Adversity Profile Response) questionnaire, AKM Number Content Questions (SAKB) (which consist of three contexts scientific, socio-cultural, and personal), and an interview guide. The analysis was based on numeracy indicators that included: identifying information and assessing the problem mathematically, using mathematical facts and procedures, and interpreting and evaluating the results. In this study, the student in the climber AQ category was able to fulfill all numeracy indicators across all question contexts. Meanwhile, the camper category student was unable to identify information and assess the problem mathematically in the scientific context. The student in the quitter AQ category met all numeracy indicators only in the personal context. These findings suggest that understanding students’ numeracy skills by considering their Adversity Quotient can help teachers plan instructional strategies that meet students’ needs. In the future, mathematics education should focus not only on improving numeracy skills but also on fostering students’ persistence and resilience in problem-solving.